Amidinato Isopropylmethylamidosilylene-catalyzed hydroboration of carbonyl compounds - Lee, Jiawen (2022)
This study describes the use of an amidinato isopropylmethylamidosilylene [LSiN(Me)iPr] (1, L = PhC(NtBu)2) to catalyze hydroboration of carbonyl compounds. Compound 1 (loading: 5 – 10 mol%) was shown to be an efficient catalyst for the chemoselective hydroboration of aldehydes (average yield = 97 %, average TOF = 8.8 h-1) and ketones (average yield = 97 %, average TOF = 1.7 h-1) with pinacolborane (HBpin) in C6D6 at 90 oC to form borate esters. Mechanistic studies shows that the Si lone pair electrons on 1 and the B vacant p orbital of HBpin activates the C=O double bond of aldehydes and ketones, the intermediates of which undergoes hydroboration to yield borate esters and regenerate compound 1.